Theories of fiscal federalism between local preferences and contemporary developments - Abid Khalid Rasul; Abdullah Kadir Fage Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The theories of fiscal federalism are a vital subject within the field of public finance. They provide a normative framework for determining the allocation of financial powers within federal systems and multi-level government systems. This study delves into the first and second generations of fiscal federalism theories, offering a comprehensive understanding of the topic and valuable insights for policymakers. The first-generation theories emerged in the mid-20th century within the context of Keynesian economics, which advocates state intervention in the economy when the market fails to provide public goods and services adequately. First-generation theories categorize the public sector into economic stability, resource redistribution, and allocation. They advocate centralization of economic stability and redistribution to achieve economic equity and efficiency, while decentralizing allocation functions to provide local public goods and services in line with local preferences. Regional governments are believed to possess better knowledge of their residents’ needs. These theories favor centralized revenue collection, leading to fiscal imbalances requiring financial transfers from national governments. The advent of economic globalization and Neoliberalism gave rise to the second generation of theories that challenge some first-generation ideas. They call for reducing the role of federal government, emphasizing market reliance, and granting more authority to regional governments. They doubt the effectiveness of federal governments in achieving economic stability and income distribution. Critics argue that relying solely on financial transfers encourages overspending and weak revenue collection by regional governments, leading to a weakened sense of responsibility. Using a descriptive and theoretical analysis approach, this research aims to explore the differences between fiscal federalism and fiscal decentralization within the context of federal systems. It investigates whether financial responsibilities between federal and regional governments are solely dependent on economic factors, especially in federal systems that incorporate shared-rule and self-rule in the political process.